Antimalarial dihydroisocoumarins produced by Geotrichum sp., an endophytic fungus of Crassocephalum crepidioides - Palangpon Kongsaeree (2018)
Three novel dihydroisocoumarin derivatives (1-3) with antimalarial, antituberculous, and antifungal activities have been isolated by bioassay-guided fractionation from an endophytic fungus, Geotrichum sp., collected from Crassocephalum crepidioides. Structures were established as 7-butyl-6,8-dihydroxy-3(R)-pent-11-enylisochroman-1-one (1), 7-but-15-enyl-6,8-dihydroxy-3(R)-pent-11-enylisochroman-1-one (2), and 7-butyl-6,8-dihydroxy-3(R)-pentylisochroman-1-one (3) using spectroscopic data.